OXIDATIVE STRESS REDUCING AND LIVER PROTECTIVE EFFICACY OF ETHYL ACETATE FRACTION ISOLATED FROM PAJANELIA LONGIFOLIA (WILLD) K. SCHUMAN - Datta, Suparna; Choudhury, Manabendra Dutta (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: We investigated the liver protective as well as oxidative stress reducing activity of isolated fractions (Pajanelia fraction-1, 2, and 3 [PF1, PF2, and [PF3]) from ethyl acetate extract of Indian medicinal plant Pajanelia longifolia (Willd.) K. Schuman. Methods: The liver protective activity of fractions was evaluated against carbon tetrachloride (CCl4) (0.5 ml/kg body weight intraperitoneal [b.w. i.p.]) induced hepatic damage in Swiss albino mice. Isolated fractions (at dose level of 150 mg/kg b.w. per orally [p.o.]) were administered to mice before 30 minutes of CCl4 administration. Silymarin at a dose of 50 mg/kg b.w. p.o. was taken as a standard drug. The liver protective activity of fractions was measured on serum biochemical parameters such as serum glutamic pyruvic transaminase, serum glutamic oxaloacetic transaminase, serum alkaline phosphatase, and bilirubin (total). Further antioxidant activity of fractions was also measured on antioxidant enzymatic and non-enzymatic levels such as reduced glutathione, lipid peroxidation, superoxide dismutase, catalase, and glutathione peroxidase. Results: The in vivo study revealed that the PF3 most effectively protected the liver from damage by CCl4. The findings were also confirmed by histopathological observations. High-performance liquid chromatography result was clearly indicated that the fraction was pure. Conclution: Ethyl acetate fraction (Pajanelia fraction 3) from P. longifolia may be considered as a liver protective agent.